Художній простір Людмили Вознюк - Пахолок, Зінаїда Олександрівна; Pakholok, Zinaida (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті схарактеризовано літературну діяльність волинського вчителя-дефектолога Людмили Вознюк, присвячену дітям з особливими освітніми потребами. Проаналізовано книжки для дошкільників: визначено жанр і зміст, виховне значення, описано їх художнє оформлення. Установлено, що з метою формування толерантного ставлення до людей з обмеженими можливостями вперше в українській літературі для дітей з’явився триптих про інвалідність. The article presents the literary activity of Volyn teacher-defectologist Lyudmila Vozniuk, which is devoted to the children with special educational needs. The series of books «Feel with the heart» are analyzed. The first book – «Let’s learn to see together» – presents the story of the blind and visually impaired children; the second one – «Hear me with the heart» – is about the deaf children and children with hearing problems; the third one – «Let’s go to the fairytale» – tells the reader about the nightingale with one wing. The genre of this fairytale was chosen for prepare preschoolers for the perception of children on wheelchairs. L. M. Vozniuk’s triptych, which is written through much suffering and dictated by the time, full of inexhaustible vitality and optimism, is a unique publication, which has no analogues in Ukraine. It forms the foundations of a tolerant attitude towards children with visual, hearing, musculoskeletal system defects and it motivates to a caring attitude to the children with disabilities as well as to overthinking of your own life values.
Lyudmila Voznyuk’s Art Space
Keywords: українська література для дітей; зарубіжна література для дітей; діти з особливими освітніми потребами; толерантність; літературно-педагогічний жанр; лист; п’єса; оповідання; казка; триптих; Ukrainian literature for children; foreign literature for children; children with special educational needs; tolerance; literary and pedagogical genre; letter; play; story; fairytale; triptych